Constructing and Evaluating an Evolving Web-API Network for Service Discovery - Adeleye, Olayinka; Yu, Jian; Yongchareon, Sira; Han, Yanbo (Service-Oriented Computing, 2018)
Web-APIs enable cross-organizational functionality integration over the Web and thus are the foundation of modern distributed service-based systems. However, despite the rapid increase in the number of Web-APIs available on the Internet, the discovery and uptake of appropriate Web-APIs by businesses on a Web scale is still a great challenge. One of the main reasons is that Web-APIs registered on directories such as ProgrammableWeb.com are in general isolated, as they are registered by diverse providers independently and progressively. In this paper, we present a method for analyzing the Web-API ecosystem and propose a complex-network-based approach for building an evolving social network for Web APIs. We conduct our analysis in two phases: First, from the complex network perspective, we investigate mashups and Web-APIs interactions and analyze the Web-API popularity distribution using the popular ProgrammbleWeb dataset. Second, we quantitatively measure the Preferential Attachment mechanism which is a key driver of an evolving network. Based on our analysis, we propose an approach to construct an evolving Web-API social network based on the theoretical procedure of the Barabási-Albert complex network model. Results presented in this work will not only provide insight into the topology of the Web-API ecosystems but also serve as a practical guide for designing an evolving-network-based solution for service discovery.